DigiMetro - An Application-Level Multicast System for Multi-party Video Conferencing - Luo, Chong; Li, Jiang; Li, Shipeng (Proceedings of IEEE Globecom'04, 2004)
The increasing demand for multi-party video conferencing has aroused the research interest in the underlying multicast support. In this paper, we propose DigiMetro, an application-level multicast system tailored to small and impromptu video conferencing. Breaking through the conventional wisdom to use shared overlay to handle multiple data sources, DigiMetro organizes the data delivery routes as source-specific trees, which are first constructed by a local greedy algorithm and then gradually improved by a global refinement procedure. Extensive simulation experiments demonstrate the efficiency of both algorithms. Moreover, DigiMetro is able to handle different video bit rates and provides with different services over voice/video streams.